Natural Gas dehydration methods-Challenges and fixes - Onuoha fidelis wopara; Nnadikwe Johnson; Momoh abdulazeez adeyemi; Stephen Oyelami (Journal Majelis Paspama, 2026)
Natural gas dehydration is a crucial process in the energy industry, ensuring pipeline quality gas that meets stringent specifications for transmission and distribution. This research examines key technologies employed in natural gas dehydration, including glycol absorption, desiccant adsorption, solvent salt adsorption, chemical cooling, and hydrate suppression. Among these, glycol absorption remains the most widely used method, particularly in large-scale gas processing operations. However, it faces significant challenges such as emissions, glycol losses, and degradation, particularly in Nigeria's gas fields and storage facilities, impacting operational efficiency and environmental compliance. Desiccant adsorption offers high dehydration efficiency, achieving very low water dew points, but requires effective regeneration strategies and is often limited to specific applications due to cost and complexity. Other methods like solvent salt adsorption, chemical cooling, and hydrate suppression have niche applications but are less prevalent for mainstream gas dehydration. This study focuses on optimizing glycol absorption systems, addressing prevalent issues, and proposing practical solutions to enhance gas processing performance. It details the technology's process flow, operational challenges, and potential fixes for improving dehydration efficiency, reducing emissions, and minimizing losses. Key aspects like glycol circulation rates, regeneration systems, and contamination management are analyzed to provide a comprehensive understanding of the process.